P08.06 Lactic acid isomers differentially reduce chlamydia trachomatis infection in a ph dependent manner. (13th September 2015) - Edwards, V; McComb, E; Guttman, H; Humphrys, M; Forney, L; Bavoil, P; Ravel, J
Abstract : Introduction: Epidemiological studies indicate that the vaginal microbiota can significantly impact the risk of acquiring sexually transmitted infections, including chlamydia. Lactobacillus spp. are the most common commensal bacteria in the healthy human vagina; they produce lactic acid to create an acidic environment with pH ranging between 3.5 and 4, thought to reduce vaginal colonisation by STI agents. However, not all species of Lactobacillus are believed to perform this function equally, and we hypothesised that species that produce low amounts or no D-lactic acid, while achieving low pH do not fully protect women. Methods: A 3D model of cervical epithelial cells (A2EN) developed in our lab was exposed to D(-), L(+) or a D/L racemic mixture of lactic acid at various concentrations to produce pH 7, 5.5 and 4 or to several Lactobacillus spp. conditioned media (LCM). Cells were infected with C. trachomatis serovar L2 for 48 h, stained and imaged by confocal microscopy. Analysis of the resultant IFUs was used to determine the number of infected host cells. Results: We observed a reduction of Chlamydia trachomatis infectivity in a pH dependent manner. Further, at pH 4, D(-) lactic acid afforded maximal protection compared to L(+) lactic acid. Interestingly, 50% infectivity is still observed with HCL at pH 4, indicating that pH alone is not responsible for this protection. Exposure of cells to conditioned media from the various Lactobacillus spp. showed that high D(-) lactic acid producing bacteria ( Lactobacillus crispatus and Lactobacillus jensenii) afforded significantly greater protection against C. trachomatis than did Lactobacillus iners, which produces predominantly L(+) lactic acid. Conclusion: These results suggest a differential role for specific species of Lactobacillus in driving resistance to C. trachomatis infections and potentially other STIs. Lactic acid isomers production should be considered when developing Lactobacillus vaginal probiotics. Disclosure of interest statement: Project funded by NIH-NIAID-STI-CRC U19 AI084044 "Eco-Pathogenomics of Chlamydial Reproductive Tract Infection". No pharmaceutical grants were received in the development of this study.